Evaluation of pelleting process parameters on feed nutrients, starch gelatinization and pig growth performance - Lewis, Landon L. (Kansas State University, 2014)
In two experiments, conditioning time and temperature of swine feed were altered to determine effects of starch, vitamin retention, and swine growth performance. A third experiment evaluated methodologies for estimating gelatinized starch in swine feed. Across all experiments, diet formulation was constant. In Exp. 1, treatments were arranged in a 2 × 3 factorial design plus a control, including 2 conditioning temperatures (77 vs. 88°C) and 3 conditioner retention times (15, 30, and 60 s). A mash diet was added for a total of 7 treatments. Total starch was affected by conditioning temperature (P = 0.04) but not time (P = 0.50). Similar results were observed for gelatinized starch (P = 0.005 and 0.65, respectively). Sample location also affected total starch (P = 0.0002) and gelatinized starch (P = 0.0001), with the greatest increase in gelatinization occurring between conditioned mash and hot pellets. Conditioning alone did not influence gelatinization as evidenced by similar values between cold and hot mash (P > 0.05). Neither conditioning temperature nor time affected vitamin concentrations (P > 0.50). A portion of these treatments were then fed to 180 nursery pigs (PIC 327 × 1050; initially 12.6kg) in an 18-d study. Treatments included: 1) non-processed mash (negative control); 2) pelleted diet conditioned for 30 s (positive control); 3) pelleted diet conditioned for 15 s and reground; 4) pelleted diet conditioned for 30 s and reground, and 5) pelleted diet conditioned for 60 s and reground. Observed growth performance differences appear to be due to feed form, not conditioning time. Average daily gain and G:F did not differ (P > 0.12) between treatments, but ADFI was decreased (P = 0.03) as expected for pigs fed the positive control pelleted diet compared to all other diets. There were no differences (P > 0.05) in any growth performance variables amongst the three conditioning temperatures. In Exp. 3, it was determined that the method developed by Mason et al. (1982) was the best indicator of gelatinization in livestock feed. In summary, feed form, but not conditioning time affected gelatinized starch and swine growth performance.
Keywords: conditioning; feed processing; gelatinization; pelleting; temperature; Agriculture, General (0473)